Simulasi Model Perpindahan Panas Pada Proses Penetasan Telur Menggunakan Software Matlab - Ro'ifah, Miftahur (Universitas Dr. Soetomo, 2025)
Abstract This study aims to analyze the heat transfer profile in the artificial egg hatching process that approaches the natural process using interface boundary conditions. Simulations are carried out by varying the temperature and length of the egg axis, with solutions using the θ-method. The steps taken include parameter identification, program creation using Matlab software, simulation, and analysis of results. The results of the study showed that the fastest heat transfer in quail eggs was at a temperature of 37°C, chicken eggs at 38°C or 39°C, and duck eggs at 37°C or 39°C. The fastest heat transfer occurred when the length of the egg axis was below average. Keywords: Egg; Heat; Matlab; θ-Method.